(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Indonesian New Exporters (INE) program is a model for export development through training from upstream to downstream. Indonesia’s handicraft export activities during the Covid-19 pandemic experienced a significant decline. A good strategy is needed in its development so that the handicraft sector MSMEs can enter the export market. This study aims to create a new exporter solution in the handicraft business sector. The method used in this paper is descriptive qualitative through learning by providing knowledge training and practice. The training includes the manufacture of new products, branding, displays, pricing, negotiations, delivery methods, completeness of export documents, and promoting handicraft products at the International Craft Exhibition. Material by preparing superior craft products according to global market demand. This research involved 20 MSMEs participants in Bantul Regency, Yogyakarta Special Region. MSMEs participants gain experience in preparing new handicraft products to export sales methods. The creation of handicraft products is adjusted to the growing trend in the world of export destinations. The results show that the training provided can increase the number of new entrepreneurs in the handicraft sector. New entrepreneurs who understand the mechanism of handicraft export can be formed correctly. INE offers clear directions for coaching and business development in the export-oriented handicraft sector. INE provides support and support in improving the community’s welfare and economy and increasing the State’s foreign exchange.